Comparison of sexual partnership characteristics and associations with inconsistent condom use among a sample of adolescents and adult women diagnosed with Chlamydia trachomatis. - Foulkes, Hillary B S; Pettigrew, Melinda M; Livingston, Kara A; Niccolai, Linda M (Journal of women's health (2002), 2009)
This analysis compared characteristics of female adolescent and adult sexual partnerships and related these characteristics to inconsistent condom use.
Keywords: Adolescent; Adolescent Behavior; Adult; Chlamydia Infections; Condoms; Contraception Behavior; Female; Health Knowledge, Attitudes, Practice; Humans; Interpersonal Relations; Questionnaires; Risk-Taking; Sexual Partners; United States; Young Adult